Pursued by a Bear: The Art of Identity in Shakespeare and Spenser - Villeponteaux, Mary (Early Theatre, 2025)
This essay explores the connection between The Winter’s Tale and The Faerie Queene, arguing that Shakespeare’s debt to Spenser is signalled by a previously unrecognized adaptation of the baby-and-bear episode from Book 6. Recognizing how Shakespeare both echoes and revises The Faerie Queene elucidates how The Winter’s Tale undermines the idea of essential identity and challenges social hierarchies. Echoes of The Faerie Queene in Shakespeare’s play and textual evidence that the same actor doubled the roles of Antigonus and Autolycus heighten Shakespeare’s criticism of the court and valorization of the power of art.